Kidney Transplantation in Patients with Atypical Hemolytic Uremic Syndrome due to Complement Factor H Deficiency: Impact of Liver Transplantation - Kim, Sejin; Park, Eujin; Min, Sang-il; Yi, Nam-Joon; Ha, Jongwon; Ha, Il-Soo; Cheong, Hae Il; Kang, Hee Gyung (Journal of Korean medical science, 2018)
Atypical hemolytic uremic syndrome (aHUS) is a rare disease that is often associated with genetic defects. Mutations of complement factor H (CFH) are the most common genetic defects that cause aHUS and often result in end-stage renal disease. Since CFH is mainly produced in the liver, liver transplantation (LT) has been performed in patients with defective CFH. The clinical courses of four kidney allograft recipients who lost their native kidney functions due to aHUS associated with a CFH mutation were reviewed. Subject A underwent kidney transplantation (KT) twice, aHUS recurred and the allograft kidney failed within a few years. Subject B received a KT and soon experienced a recurrence of aHUS coinciding with infection. Her allograft kidney function has worsened, and she remains on plasma infusion therapy. Subject C underwent LT followed by KT. She is doing well without plasma infusion therapy after combined LT-KT for 3 years. Subject D received KT following LT and is now recurrence-free from aHUS. In patients with aHUS associated with a CFH mutation, KT without LT was complicated with a recurrence of aHUS, which might lead to allograft loss. Conversely, LT was successful in preventing the recurrence of aHUS and thus might be another option for a recurrence-free life for aHUS patients associated with CFH mutation.